Effectiveness of Aloe vera versus Glibenclamide on Serum Lipid Parameters, Heart and Skin Lipid Peroxidation in Type-II Diabetic Rats - OZSOY, NURTEN; YANARDAG, REFIYE; CAN, AYSE; AKEV, NURIYE; OKYAR, ALPER (Asian Journal of Chemistry, 2010)
Many secondary plant metabolites have been reported to possess lipid-lowering properties. Aloe vera which has been extensively used for medical and cosmetic purposes contains multiple constituents with potential biological activities. This study was undertaken to investigate the beneficial effects of Aloe vera extracts in comparison to glibenclamide on serum lipid parameters, liver glycogen and on heart and skin lipid peroxidation. Type II diabetes was induced by 100 mg/kg, streptozotocin injection to neonatal rats (n0-STZ). The diabetic rats were separated into four groups and each group was given the following samples by gavage, daily for 15 d: I. Diabetic (Control): 6 mL/kg phosphate buffered saline (PBS); II. Diabetic + Aloe gel: 10 mL = 63 mg/kg Aloe vera leaf gel extract; III. Diabetic + Aloe pulp: 500 mg/kg Aloe pulp extract; IV. Diabetic + Glibenclamide: Glibenclamide (1 mg/kg). On day 15, blood and liver, skin and heart tissues were taken from each rat. In diabetic group given A. vera extracts, serum total cholesterol, LDL-cholesterol, atherogenic index (AI), total lipid, sialic acid, skin and heart tissues lipid peroxidation (LPO) levels decreased, whereas serum HDL-cholesterol, liver glycogen, serum total protein levels increased, in comparison to diabetic controls. In the diabetic group given glibenclamide, AI and heart LPO which were diminished in Aloe given groups were rised, whereas HDL-cholesterol, liver glycogen which were increased in Aloe groups were reduced. These results reveal that diabetes mellitus increased oxidative damage in skin and heart tissue and that Aloe vera has an ameliorating effect better than glibenclamide on the oxidative stress via its antioxidant property. The administration of A. vera extracts may be also able to reduce hyperlipidemia which is one of the complications related to the risk of diabetes.